Rapid culture-based diagnosis of pulmonary tuberculosis in developed and developing countries - Asmar, Shady; Drancourt, Michel (Frontiers in Microbiology, 2015)
Culturing Mycobacterium tuberculosis remains the gold standard for the laboratory diagnosis of pulmonary tuberculosis, with 9 million new cases and 1.5 million deaths mainly in developing countries. Reviewing data reported over 20 years yields a state-of-the-art procedure for the routine culture of M. tuberculosis in both developed and developing countries. Useful specimens include sputum, induced sputum and stools collected in quaternary ammonium preservative-containing sterile cans. The usefulness of other non-invasive specimens remains to be evaluated. Specimens can be collected in a diagnosis kit also containing sampling materials, instructions, laboratory requests and informed consent. Automated direct LED fluorescence microscopy after auramine staining precedes inoculation of an egg-lecithin-containing culture solid medium under microaerophilic atmosphere, inverted microscope reading or scanning video-imaging detection of colonies and colonies identification by recent molecular methods. This procedure should result in a diagnosis of pulmonary tuberculosis as fast as 5 days. It may be implemented in both developed and developing countries with automated steps replaceable by manual steps depending on local resources.